Isolation of Human Third Molar Dental Pulp Stem Cells and Their Characteristics Before and After Cryopreservation - Mazur, Svitlana; Rogulska, Olena; Revenko, Olena; Volkova, Nataliya; Petrenko, Oleksandr (Problems of Cryobiology and Cryomedicine, 2021)
Dental pulp stem cells (DPSCs) from human third molar tooth germ (wisdom tooth) were isolated using a collagenasebased enzymatic method, the obtained cells were analyzed as for morphology in monolayer culture, immunophenotype, proliferation and differentiation potential before and after cryopreservation. In this study, we showed that based on morphological features, surface markers profile and differentiation potential, the isolated DPSCs corresponded to multipotent mesenchymal stromal cells. DPSCs cryopreservation by slow cooling (1 °С / min) down to –80°C with subsequent immersion into liquid nitrogen in cryoprotectant-free culture medium led to cell death. Cryopreservation using the same protocol in the presence of 10% dimethyl sulfoxide (DMSO) and 20% serum ensured (82 ± 6)% cell viability; while metabolic and proliferative activity, as well as the ability to differentiate into the osteo- and adipogenic lineages of cryopreserved DPSCs were similar to their non-cryopreserved counterparts. Probl Cryobiol Cryomed 2021; 31(1): 058–069